138k views
5 votes
Solve h^2− 42 = −h using the quadratic formula.

A. h = 0 or h = 7
B. h = −6 or h = 7
C. h = 6 or h = −7
D. h = −6 or h = −7

User Franke
by
6.4k points

2 Answers

1 vote

Answer:

c mydude

Explanation:

User John Pittaway
by
6.1k points
4 votes
Hi there! The answer is C. h = 6 or h = −7


{h}^(2) - 42 = - h
Add h to both sides of the equation.


h {}^(2) + h - 42 = 0
First we need to find the discriminant (which can be found using the formula D = b^2 - 4ac)


d = 1 {}^(2) - 4 * 1 * - 42 \\ d = 1 + 168 \\ d = 169

Now we can plug in our found values into the quadratic formula.


x = ( - b - √(d) )/(2a) \: \\ or \\ \: x = ( - b + √(d) )/(2a)

Plug in.

x = ( - 1 - √(196) )/(2 * 1) = ( - 1 - 13)/(2) = ( - 14)/(2) = - 7 \\ or \\ x = ( - 1 + √(196) )/(2 * 1) = ( - 1 + 13)/(2) = ( 12)/(2) = 6

Hence, the answer is C. h = 6 or h = −7
User Keloo
by
6.0k points